Distributed Event-Triggered Control of Multiagent Systems with General Linear Dynamics - Xieyan Zhang; Jing Zhang (Journal of Control Science and Engineering)
This paper discusses the event-triggered consensus problem of multiagent systems. To investigate distributed event-triggering strategies applied to general linear dynamics, we employ a dynamic controller to convert the general linear dynamic to the single-integrator model by a change of variable. The consensus value of these new states is a constant so that the distributed event-triggering scheme is obtained under periodic event detections, in which agents with general linear dynamics require knowledge only of the relative states with their neighbors. Further, an event-triggered observer is proposed to address the case that only relative output information is available. Hence, the consensus of both the state-based and observer-based cases is achieved by the distributed event-triggered dynamic controller. Finally, numerical simulations are provided to demonstrate the effectiveness of theoretical results.